Module number of default mode network: Inter-subject variability and effects of sleep deprivation - Wang, Yulin; Liu, Huan; Hitchman, Glenn; Lei, Xu (Brain research, 2015)
Sleep deprivation have shown its great influence on the default mode network (DMN). The DMN is a core system in resting state brain activity. Recent studies have focused on its subsystems and multiple functions. However, the individual specific organization of the DMN is rarely investigated. As the effects of sleep deprivation (SD) on mood are well documented, a more interesting question is whether changes in the processing of emotional information due to sleep deprivation are related to any specific topological properties of the DMN. In this study, we proposed an index, module number of DMN (mnDMN), to measure the specific modular structure of the DMN for each individual. Our results showed that the DMN was generally split into two modules after SD, and the decreased functional connectivity between the two modules was related to a worsening of the participants׳ self-reported emotional state. Furthermore, the mnDMN was correlated with participants’ rating scores of high valence pictures in the SD session, indicating that the mnDMN might reflect mood valuation in the human brain. Overall, our research reveals the diversity of the DMN, and may contribute towards a better understanding of the properties and functions of the DMN. •Sleep deprivation induced DMN splitted into two subsystems according to the principle of modularity on the group level.•The module number of DMN (mnDMN) was proposed to measure the heterogeneity of DMN among individuals.•Participant with a larger mnDMN reported higher rating scores of emotive pictures.•The diversity of the DMN unveils the changed processes in emotional information due to sleep deprivation.